Evidence for the genetic similarity rule at an expanding mangrove range limit. Issue 8 (29th August 2021) - Kennedy, John Paul; Antwis, Rachael E.; Preziosi, Richard F.; Rowntree, Jennifer K.
Abstract: Premise: Host‐plant genetic variation can shape associated communities of organisms. These community‐genetic effects include (1) genetically similar hosts harboring similar associated communities (i.e., the genetic similarity rule) and (2) host‐plant heterozygosity increasing associated community diversity. Community‐genetic effects are predicted to be less prominent in plant systems with limited genetic variation, such as those at distributional range limits. Yet, empirical evidence from such systems is limited. Methods: We sampled a natural population of a mangrove foundation species ( Avicennia germinans ) at an expanding range limit in Florida, USA. We measured genetic variation within and among 40 host trees with 24 nuclear microsatellite loci and characterized their foliar endophytic fungal communities with internal transcribed spacer (ITS1) gene amplicon sequencing. We evaluated relationships among host‐tree genetic variation, host‐tree spatial location, and the associated fungal communities. Results: Genetic diversity was low across all host trees (mean: 2.6 alleles per locus) and associated fungal communities were relatively homogeneous (five sequence variants represented 78% of all reads). We found (1) genetically similar host trees harbored similar fungal communities, with no detectable effect of interhost geographic distance. (2) Host‐tree heterozygosity had no detectable effect, while host‐tree absolute spatial location affected community alpha diversity. Conclusions: This research supports the genetic similarity rule within a range limit population and helps broaden the current scope of community genetics theory by demonstrating that community‐genetic effects can occur even at expanding distributional limits where host‐plant genetic variation may be limited. Our findings also provide the first documentation of community‐genetic effects in a natural mangrove system.